Does Formal Credit Work for MOOC-Like Learning Environments? - Kursun, Engin (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
Although a number of claims have been made describing massive open online courses (MOOCs) as a disruptive innovation in education, these claims have not yet been proven through research. Instead, MOOCs should perhaps be considered as an integrative model for higher education systems, but to do so will require recognition of credentials. Initial experiments of MOOCs were not offer academic credit, but recently there have been some attempts to offer course credit for MOOCs or MOOC-like courses. However, does earning a credit will affect students’ performance and behavior in MOOCs has not been explored closely. Therefore, the aim of this study is to assess the effect of crediting on students’ achievement, perceived intrinsic and extrinsic goal orientations, and perceived course value. A causal comparative research design was applied. Data was collected via 516 responses to an online survey and achievement tests. Three credit conditions were compared: credit bearing, non-credit bearing, and credit careless. ANOVA results showed a significant difference between the credit bearing groups and non-credit bearing groups for all dependent variables. The credit bearing group also scored significantly higher achievement scores than the credit careless group. Credit clearly and significantly affected all dependent variables investigated in this study. Therefore, various possible models can be adopted by higher education institutions to integrate MOOCs as a credit. Further studies can explore the effects of credit on students’ online behaviors, such as engagement with online activities and user events on MOOC platforms.